Decreased right ventricular strain before LVAD implantation is associated with adverse early outcome. (25th November 2020) - Tan, T.S; Lin, G; Pislaru, S.V; Luis, S.A; Frantz, R.P; Clavell, A.L; Stulak, J.M; Pislaru, C; Brady, P; Liu, M; Ye, Z
Abstract: Objectives: Right ventricular (RV) failure occurring after left ventricular assist device (LVAD) implantation is associated with increased mortality. Purpose: We sought to determine whether RV strain by echocardiography predicts outcomes following LVAD. Methods: Consecutive patients who underwent continuous flow LVAD placement at our clinic between February 2007 and October 2018 were included. Patients with complex congenital heart disease and arrhythmogenic right ventricular cardiomyopathy were excluded. Baseline characteristics, pre-operative hemodynamic catheterization (1 week) transthoracic echocardiography (1 month) measurements were obtained from the medical record. Speckle tracking RV free wall longitudinal 2D strain was measured using TomTec Imaging System. Univariate and multivariable analysis performed to identify predictors of mortality following LVAD. Results: The study group was comprised of 323 patients (mean age 60.8±11.5, 79.9% male) of which 256 had adequate image quality for RV strain. RV strain was impaired in most patients (mean −11.7±3.47). RV strain of −8.1% was identified as predictive of poor outcomes. RV strain did not correlate with other measures of RV dysfunction including pulmonary artery pulsatility index (PAPi) and RVFAC. After adjusting for PAPi, RA pressure, and clinical cumulative risk scores (Matthews, Kormos and Lietz-Miller) impaired RV free wall longitudinal strain (OR: 1.14; 95% CI: 1.01–1.29, p=0.025), tricuspid regurgitation (by vena contracta width (TRvc) (OR: 1.19; 95% CI: 1.05–1.36, p=:0.0021) and smaller LVEDD (OR: 0.95; 95% CI: 0.92–0.99, p:0.023) predicted 30-day all-cause mortality and RV failure. Decreased RV free wall strain also predicted peri-operative mortality (22.58% vs. 4.89%, p=0.0003) and prolonged inotropic support (247.0.±277.4 vs. 122.8±139.3, p=0.024). Conclusions: RV free wall strain is a non-invasive independent predictor of 30-day adverse outcomes (RV failure or all-cause mortality) Routine measurement of RV free strain may identify those patients at highest risk for early and long term mortality following LVAD. Funding Acknowledgement: Type of funding source: None